Effects of physical activity on cognitive function in healthy university students - Tan, Jin Han (2016)
The purpose of this study was to examine the effects of physical activity on cognitive function in healthy university students. Physical activity has been shown to improve cognitive function, in terms of feelings and cognitive performance, over time. This study hypothesized that physical activity will improve cognitive function over time, and that the physical activity with a relatively higher exercise intensity will show more improvement. In the present study, a group of 20 healthy undergraduates from Nanyang Technological University (10 male, 10 female; M age = 22.7 years, SD = 1.34; M body mass index = 21.2, SD = 2.02) were randomly selected and sorted into two groups. They participated in jump rope and walking at moderate intensity over two activity sessions. Findings showed significant differences in heart rate (p = < .001) and rate of perceived exertion (p = < .001). Furthermore, the scores of feeling scale (p = .002), felt arousal scale (p = .007), Stroop task (p = < .001) and Remote Associates Test (p = < .001) were significantly better post-activity as compared to pre-activity. In conclusion, students’ cognitive performance improved, and more positive experiences were reported post-activity compared to pre-activity, while no differences were observed between activities.